Web vulnerabilities: identifying patterns and remedies. Issue 2 (February 2016) - Muscat, Ian
Abstract : Nearly half of all websites have high security vulnerabilities, many simple to fix and often with legacy bugs that were thought to be consigned to history, according to new research. In addition, such vulnerabilities mean that over half of the organisations scanned fail to meet PCI compliance requirements. Nearly half of all websites have high-risk security vulnerabilities, many simple to fix and often with legacy bugs that were thought to be consigned to history, according to new research. Ian Muscat of Acunetix takes us through the research and concludes that, far from reducing the risks, companies are taking too casual an approach and vulnerabilities are now worse than ever. CSOs and CISOs need to take immediate preventative action as this problem of unsecured apps will only get worse as new technologies are adopted.